Truth and Tension in Science and Religion - Raman, Varadaraja V. (Center Ossipee, New Hampshire : Beech River Books, 2009)
"An examination of the frameworks of science and religion that provides a multi-cultural view of how they affect our perception of the truth"--Provided by publisher.
Introduction -- On science and religion -- Epistemological aspects -- Explanatory dimensions -- Belief systems and God -- Spiritual aspects -- Ethical aspects -- Dissimilar visions on common themes -- Origins and ends -- Concluding thoughts.
Includes bibliographical references (p. 340-366) and index.
Keywords: Religion and science